2020
DOI: 10.1016/j.jclepro.2020.123039
|View full text |Cite
|
Sign up to set email alerts
|

A roadmap investment strategy to reduce carbon intensive refrigerants in the food retail industry

Abstract: High global warming potential (GWP) refrigerant leakage is the second-highest source of carbon emissions across UK supermarket retailers and a major concern for commercial organizations. Recent stringent UN and EU regulations promoting lower GWP refrigerants have been ratified to tackle the high carbon footprint of current refrigerants. This paper introduces a data-driven modelling framework for optimal investment strategies supporting the food retail industry to transition from hydrofluorocarbon (HFC) refrige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…To satisfy heating demand supermarkets are exploring heat recovery methods from their refrigeration systems so they can displace natural gas related emissions, although matching supply and demand is a persistent issue that requires thermal storage [14]. With regards to minimising the impact of carbon intensive refrigerants advanced performance indicators championing energy efficiency and leakage reduction is advocated [15] as well as the phasing out of HFC refrigerants by increasing the uptake of natural refrigerants [16]. Lastly, it seems decarbonising transport fleets is a more challenging endeavour, where exploring alternative fuels to diesel such as LNG or biomethane is being considered, however the refuelling infrastructure to supply low carbon fuels is a major roadblock [17].…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy heating demand supermarkets are exploring heat recovery methods from their refrigeration systems so they can displace natural gas related emissions, although matching supply and demand is a persistent issue that requires thermal storage [14]. With regards to minimising the impact of carbon intensive refrigerants advanced performance indicators championing energy efficiency and leakage reduction is advocated [15] as well as the phasing out of HFC refrigerants by increasing the uptake of natural refrigerants [16]. Lastly, it seems decarbonising transport fleets is a more challenging endeavour, where exploring alternative fuels to diesel such as LNG or biomethane is being considered, however the refuelling infrastructure to supply low carbon fuels is a major roadblock [17].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Hart et al (2020) considered a modeling framework for maximum investment strategies that support the food retail industry in shifting from hydrofluorocarbon (HFC) refrigeration systems to lower GWP systems by 2030, in line with EU legislation, resulting in up to a 70 % annual reduction in yearly carbon emissions by 2030. Some authors, like Wang et al (2021), propose defining a clear refrigerant dosage scheme for future refrigerant replacement phasing-out.…”
Section: Climate Change and (Food) Transportation (And Vice Versa)mentioning
confidence: 99%
“…These impacts clearly identify a need for climate action (SDG 13) associated with GHG emissions and ozone layer depletion linked with storage/retail [53]. One approach is shifting from hydrofluorocarbon refrigeration systems to systems with lower impact on climate change, in line with the EU legislation [54]. In addition, a simulation of sustainability of perishable food supply chains revealed that perishability of food may increase various environmental impacts up to 120% [55].…”
Section: Impact Of Food Traders On Achieving Un Sdgs (And Vice Versa)mentioning
confidence: 99%